Republic of Armenia Leveling the STEM Playing Field for Women : Differences in Opportunity and Outcomes in Fields of Study and the Labor Market - World Bank (World Bank, Washington, DC, 2017)
This report summarizes the challenges facing Armenian women at school and in the workplace with a special focus on STEM-related employment. As the world transitions to an increasingly digital economy, jobs in science, technology, engineering, and mathematics (STEM) will become a powerful driver of economic growth in the twenty-first century. Changes in economic productivity brought through technological innovation require countries to focus on STEM; these high-productivity fields are increasingly in demand in the global economy, and are the key to competitiveness and gross domestic product (GDP) growth.Parity between men and women was one of the major achievements of socialist regimes in Eastern Europe and Central Cultural stereotypes about the types of work women should engage in and their responsibilities at home present the strongest barrier to equality between women and men in Armenia Asia. Although access, enrolment, and achievement rates are gender-equal in Armenia, women and girls tend to self-select out of STEM education tracks and career fields. At the level of education institutions, policy actions can address issues of access, information, biases, and system-wide changes to promote gender neutrality. In the short term, schools can engage teachers and students in discussions about the benefits of STEM fields of study and careers, encourage girls to embrace their interest in math and science, and provide positive role models of women who work in STEM careers. Policy action can help women make the school-to-work transition and promote their career advancement once they are working. At a national level, policy and regulatory actions can address systemic issues of bias, market failure, and information. Even at this level, some quick wins are feasible. The government may consider whether public information campaigns are needed to promote positive aspects of STEM careers to students in middle school and above, such as greater income, flexibility, and status, as well as launch a media campaign to promote and celebrate positive female role models in STEM. STEM sectors are an important source of growth for Armenia given the country’s geography and closed borders. Also, considering Armenia’s adverse demographic trends, lifting women’s participation in key growth potential sectors, including STEM, is increasingly critical.